Baiser la littérature - RER Q collectif d’autriX (Glad!)
RER Q is a collective of Paris-based queer feminist authors who write the unrepresentable, the explicit, the tender, the raw, and the erotic. In their performances, multiple bodies and voices are drawn together in space, exploding the edges of the literary text. In this selection of writing, an archive of a performance given at the feminist festival Comme Nous Brûlons, food touches science fiction, dildos and membranes proliferate, hearts break and every fictional hero is a dyke.